Pengelolaan Pembelajaran Matematika Sekolah Standar Nasional - Sutama Sutama; Kucisti Ike Retnaningtyas Suryo Putro (Universitas Pekalongan, 2013)
The general objectives of this study are to describe mathematics learning management at National Standard School of Junior High School 1 Karangkobar Banjarnegara. Then, the specific objectives are to describe the characteristics of its (1) room and media, (2) material and (3) mathematics learning interaction. This qualitative research uses observation, in-depth interviews, and documentation for collecting the data. Informants are from mathematics teachers, teachers who like and dislike mathematics, and the students. Data are analyzed by using single site in the frame of flow method qualitative analysis. Method and source triangulation are used to measure the data validity.The results show (1) room management creates effective and productive mathematics learning and media management increases motivation and concept understanding, (2) holistically learning material management results optimal learning outcome and variation in learning material develops the reflective thinking of students, (3) interaction management makes the learning process lively and happily and finally the goals are reached.